Evaluation of Erosion Intensity and Some of Its Consequences in Vineyards from Two Hilly Environments Under a Mediterranean Type of Climate, Italy - Corti, Giuseppe; Cavallo, Eugenio; Cocco, Stefania; Biddoccu, Marcella; Brecciaroli, Giorgia; Agnelli, Alberto (IntechOpen, 2011)
None